Language Politeness Among Adolescents: Sociolinguistic Study - Koni Hasa Enda Citra; Kasmantoni Kasmantoni; Heny Friantary (Yayasan Karinosseff Muda Indonesia, 2021)
The problem raised in this study is how to comply with the principles of politeness in language and is there a violation of the principles of politeness in language among teenagers in Telaga Dewa V RT 15 Bengkulu City in terms of communicating and interacting. The purpose of this study is to describe the adherence to the principles of language politeness and violations of the principles of language politeness among adolescents in Telaga Dewa V RT 15 Bengkulu City in terms of communicating and interacting. This type of research is descriptive qualitative research. The subject of this study is the act of politeness in language performed by teenagers in Telaga Dewa V, RT 15, Bengkulu City in the form of conversation or interaction. While the informants in this study were several teenagers who lived in Telaga Dewa V, RT 15, Bengkulu City. Data collection techniques in the form of observation, documentation and interviews. The results of this study conclude that there are four maxims that are obeyed by adolescents in Telaga Dewa V, RT 15, Bengkulu City, namely tact maxim, generosity maxim, approbation maxim and modesty maxim which consists of 23 utterances. There were four violations of the principle of politeness in language at Telaga Dewa V, RT 15, Bengkulu City, namely the maxim of wisdom, the maxim of generosity, the maxim of appreciation/praise and the maxim of simplicity/humility which consists of 11 utterances.